Wales and the American dream - Tyler, Robert Llewellyn (Cambridge Scholars Publishing, 2015)
The Welsh comprised a distinct and highly visible ethno-linguistic group in many areas of the United States during the late decades of the nineteenth century and the early decades of the twentieth. Through a consideration of settlement patterns, cultural and religious institutions, language retention, and marriage preference, this book provides a micro-study of four identifiable Welsh communities over a set period of time. The nature, strength and long-term viability of these communities is analysed and assessed, as are the ways in which they changed; a process which saw the Welsh become Welsh-Americans and, ultimately, Americans. Welsh immigrants in the USA were invariably portrayed as models of American citizenship by virtue of their perceived national characteristics and their standards of social behaviour. This book tests the assumption that the Welsh were prime illustrations of the American Dream by analysing one facet of that dream; socio-economic success as revealed by occupational mobility. To what extent did the Welsh as a group occupy a privileged position in the occupational hierarchy, and were they able to maintain and improve upon their social and economic position in a relatively short space of time?